2005
DOI: 10.1111/j.1420-9101.2004.00855.x
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary genetics of egg size plasticity in a butterfly

Abstract: The evolution of phenotypic plasticity requires that it is adaptive, genetically determined, and exhibits sufficient genetic variation. For the tropical butterfly Bicyclus anynana there is evidence that temperature‐mediated plasticity in egg size is an adaptation to predictable seasonal change. Here we set out to investigate heritability in egg size and genetic variation in the plastic response to temperature in this species, using a half‐sib breeding design. Egg size of individual females was first measured a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 61 publications
3
42
0
1
Order By: Relevance
“…The presence of genetic variation for phenotypic plasticity supports the growing consensus that phenotypic plasticity itself is a genetic trait (Scheiner 1993;Scheiner and Yampolsky 1998) and that the reaction norm approach provides a valuable approach to studying its genetics (Loeschcke et al 1999;Steigenga et al 2005;Gutteling et al 2007). Genetic variation for temperature response has been reported for several species (Hassall et al 2006;Seko et al 2006;Gutteling et al 2007), but seems to be lacking in others (Fischer et al 2004;Azevedo et al 1996).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The presence of genetic variation for phenotypic plasticity supports the growing consensus that phenotypic plasticity itself is a genetic trait (Scheiner 1993;Scheiner and Yampolsky 1998) and that the reaction norm approach provides a valuable approach to studying its genetics (Loeschcke et al 1999;Steigenga et al 2005;Gutteling et al 2007). Genetic variation for temperature response has been reported for several species (Hassall et al 2006;Seko et al 2006;Gutteling et al 2007), but seems to be lacking in others (Fischer et al 2004;Azevedo et al 1996).…”
Section: Discussionmentioning
confidence: 90%
“…The degree of plasticity is defined as the slope of a reaction norm, i.e., a steeper relationship is considered to be more plastic ( de Jong 1990). A large number of laboratory experiments and quantitative genetic studies have demonstrated that there is genetic variation among individuals and populations in the steepness and elevation of thermal reaction norms (Loeschcke et al 1999;Steigenga et al 2005;Driessen et al 2007;Gutteling et al 2007;van Asch et al 2007;Liefting and Ellers 2008;Bahrndorff et al 2009). Such variation is possibly caused by biochemical differences in metabolic enzymes (Hochachka and Somero 2002) or by differences in gene expression (Schlichting and Smith 2002;Li et al 2006;Ellers et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…They may, for example, be of similar shape but with different temperatures of maximum performance, i.e., shifted horizontally along the temperature axis (e.g., the ovariole number in the fruit fly Drosophila ananassae, Yadav & Singh, 2005). They can also be of similar shape but shifted vertically along the performance axis, implying that some individuals perform faster or bigger at all temperatures (e.g., egg size in the tropical butterfly Bicyclus anynana, Steigenga et al, 2005). Finally, reaction norms can also differ in shape, for example steep reaction norms over a relatively narrow temperature interval with a high maximum performance versus flat reaction norms over a broad temperature range with lower maximum performance (e.g., body size in Drosophila melanogaster, David et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The butterfly B. anynana belongs to a group of the Lepidoptera in which vitellogenesis and choriogenesis seem to depend exclusively on JH (Ramaswamy et al, 1997). Reproduction, including different strategies in response to prevailing temperatures, has been extensively studied in B. anynana (Fischer et al, 2003a;Fischer et al, 2004;Fischer et al, 2003b;Steigenga et al, 2005), but its hormonal control is hitherto only poorly understood (Steigenga et al, 2006), making this species another suitable model. Given the dependence of reproduction on JH in both species, we here examine the effect of the NMDA receptor antagonist MK-801 on lifetime fecundity and egg size, on in vitro and in vivo JH biosynthesis, and its interactions with JH mimics.…”
Section: Introductionmentioning
confidence: 99%